Pengaruh Suhu Tinggi terhadap Perkembangan Organ Reproduksi Jantan pada Cabai (Capsicum annum L.) cv. Tanjung-2 - Iriawati Iriawati; Isqim Oktaviani; Ahmad Faizal (Jurnal Ilmu Pertanian Indonesia, 2020)
The development of male reproductive organ in plants is seriously affected by the adverse abiotic stresses. In this study, we investigated pollen development, particularly at microsporogenesis and micro gametogenesis stages of chili pepper (Capsicum annuum) cv. Tanjung-2 upon exposure with high temperature (day/night = 36/33°C). For this objective, anther of different flower sizes ranging from <2.5 mm; 3-4.5 mm; 4.5-7 mm; to 7-11 mm from treated and non-treated plants were collected. The results revealed that the early microsporogenesis stage was highly sensitive to high temperature indicated by a low progression of cells into subsequent process in meiotic division. This result was followed by the inhibition of tetrad formation up to 2%. Consequently, plant produced smaller microscpores and pollens with thin exin that resulted in the decreased pollen viability to 90%. In conclusion, high temperature has negative impact on the development of male reproductive program in chili pepper, including microsporogenesis and micro gametogenesis. Extending approach should be allocated to overcome this problem so that such environmental stress would not decrease the productivity of chili pepper. Keywords: Capsicum annuum, high temperature, microgametogenesis, microsporogenesis